2014
DOI: 10.1371/journal.ppat.1004172
|View full text |Cite|
|
Sign up to set email alerts
|

Both α2,3- and α2,6-Linked Sialic Acids on O-Linked Glycoproteins Act as Functional Receptors for Porcine Sapovirus

Abstract: Sapovirus, a member of the Caliciviridae family, is an important cause of acute gastroenteritis in humans and pigs. Currently, the porcine sapovirus (PSaV) Cowden strain remains the only cultivable member of the Sapovirus genus. While some caliciviruses are known to utilize carbohydrate receptors for entry and infection, a functional receptor for sapovirus is unknown. To characterize the functional receptor of the Cowden strain of PSaV, we undertook a comprehensive series of protein-ligand biochemical assays i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 46 publications
(118 reference statements)
7
70
0
Order By: Relevance
“…Susceptibility to human sapoviruses is not associated with histo-blood group antigen (HBGA) phenotypes (214). In vitro data also support no binding of sapovirus to HBGAs (257,258). This differs from the case for the prototype norovirus (Norwalk virus): certain HBGA phenotypes (e.g., nonsecretor) of an individual are clearly related to resistance to virus infection (259,260).…”
Section: Transmission Route and Host Susceptibilitymentioning
confidence: 86%
See 1 more Smart Citation
“…Susceptibility to human sapoviruses is not associated with histo-blood group antigen (HBGA) phenotypes (214). In vitro data also support no binding of sapovirus to HBGAs (257,258). This differs from the case for the prototype norovirus (Norwalk virus): certain HBGA phenotypes (e.g., nonsecretor) of an individual are clearly related to resistance to virus infection (259,260).…”
Section: Transmission Route and Host Susceptibilitymentioning
confidence: 86%
“…Other different genogroups/genotypes of norovirus strains can also bind to HBGAs (113,(261)(262)(263) but lack a clear relatedness between the HBGA phenotypes and resistance to infection (264)(265)(266). Sialic acids have recently been reported as binding factors for porcine sapovirus (258).…”
Section: Transmission Route and Host Susceptibilitymentioning
confidence: 99%
“…Since the P2 region of caliciviruses is the most protruding part of VP1 and is highly variable, it has been considered responsible for binding to host receptors (52). A recent study indicated that the ␣2,3-and ␣2,6-linked sialic acids on O-linked glycoproteins are receptors on LLC-PK cells for the PoSaV Cowden strain (53). In our study, based on their locations in the structural model, amino acid position 178 was located in the S domain, which may influence VP1 oligomerization, virion assembly, and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro experiments with synthetic glycoconjugates with relevance as CV receptors have revealed at least three distinct patterns of virus recognition [17] . While human NoV, ReCV/TV and bovine NoV all utilize HBGAs; other CVs such as feline CV and porcine sapovirus utilize sialic acid via N-and O-linked glycoproteins, respectively; and murine NoV uses sialic acid in a strain-dependent manner [17,18] .…”
Section: Recognition Patternsmentioning
confidence: 99%